The Genetic parameters of fertility traits in Murrah buffaloes: Estimate Genetic parameters - Sharma, Smriti; Dhaka, Surender; Patil, Chandrashekhar Santosh (Indian Journal of Dairy Science, 2023)
The data pertaining to 662 Murrah buffaloes of 24 years (1996-2019) collected from history cum pedigree sheets maintained at Buffalo Farm, department of LPM, LUVAS, Hisar studied to determine the influence of non-genetic factors viz. period, season and parity and to estimate the genetic parameter of fertility performance traits using mixed linear model. The traits studied wereage at first calving (AFC), service period (SP), conception rate (CR), calving interval (CI), number of services per conception (NSC) and pregnancy rate (PR). Period of calving had non-significant effect on all fertility traits viz. SP, CR, CI, NSC and PR, except AFC. Season of calving reported to have highly significant (P<0.01) effect on SP, NSC and PR and significant (P<0.05) effect of season of calving was obtained on CR and CI. Highly (P<0.01) significant effect of parity was reported on SP and NSC and significant effect of parity at P<0.05 was also seen on CR, CI and PR. The least squares means of AFC, SP, CR, CI, NSC and PR were 1345.75±13.88 days, 153.87±4.34 days, 67.08±1.18 %, 459.53±4.50 days, 2.01±0.05 and 0.27±0.01 %, respectively. The heritability estimates among traits in overall lactation fertility traits viz. AFC, SP, CR, CI, NSC and PR were 0.36±0.21, 0.11±0.03, 0.09±0.02, 0.23±0.10, 0.04±0.01 and 0.07±0.01, respectively. PR had negative genetic and phenotypic correlations with SP, CI and NSC whereas positive genetic and phenotypic correlation with CR. It was concluded that selective breeding and better management can led to enhancement in performance of buffaloes.